Posterior Meniscal Root Repair Using a Meniscal Suture Device - José Leonardo Rocha de Faria, M.D.; Douglas Mello Pavão, M.D., M.Sc.; Igor Stefano Menescal Pedrinha, M.D.; Eduardo Branco de Sousa, M.D., M.Sc., Ph.D.; João Matheus Guimarães, M.D., M.Sc., Ph.D.; Berliet Assad Gomes, M.D., M.Sc.; Alan de Paula Mozella, M.D., M.Sc. (Arthroscopy Techniques, 2020)
A greater understanding of the deleterious consequences that a meniscal root tear brings to the knee joint and how its surgical repair can be advantageous over the previously used treatment strategies brings the need for the development of surgical techniques that make the procedure less complex and more reproducible. When meniscal root rupture occurs, a mechanical overload occurs in the affected compartment similar to a total meniscectomy. Several authors have concluded that meniscal root reinsertion significantly improves postoperative outcomes and patient satisfaction, regardless of age or laterality of the meniscal injury. The Meniscus 4 A-II device (Rio de Janeiro, Brazil) allows stitching at the root of the medial and lateral menisci. In this article, we describe the surgical repair technique for posterior-medial and -lateral meniscal root tears using this meniscal suture device. This technique is fast and effective.